PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PT. FUMINDO ABDI LESTARI MEDAN - Ike Rukmana Sari; Syofyan Syofyan (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
The purpose of this study is to get empirical evidence whether the work environment, work discipline, and job satisfaction have an influence to the employees’ performance at PT. Fumindo Abdi Lestari-Medan. The sample of the study is 35 employees from population which is 40 employees at PT. Fumindo Abdi Lestari-Medan. The software program of Statistical Product and Service Solution (SPSS) version 2.00 is used to analyze data gained from questionnaire. The result shows that the work environment has a significant positive effect to the employees’ performance and job satisfaction as well at PT. Fumindo Abdi Lestari Medan with value of R2 equal to 0.925 or 92%. Hence, the model can be used for estimation activity or in decision of company to improve employees’ performance. Partially, the value of coefficient value of variables whose value is different from one to another is the working environment which is 0.953. While work discipline is 0.032 and Job satisfaction is that of 0.086 which is the value of the independent variable will affect the value of performance of change at times with the coefficient value